A 0.6‐V sub‐mW X‐band RFSOI CMOS LNA with novel complementary current‐reused technique. (7th March 2017) - Dai, Ruofan
Summary: A fully integrated 0.6 V low‐noise amplifier (LNA) for X‐band receiver application based on 0.18 μm RFSOI CMOS technology is presented in this paper. To achieve low noise and high gain with the constraint of low voltage and low power consumption, a novel modified complementary current‐reused LNA using forward body bias technique is proposed. A diode connected MOSFET forward bias technique is employed to minimize the body leakage and improve the noise performance. A notch filter isolator is constructed to improve the linearity of low voltage. The measured results show that the proposed LNA achieves a power gain of 11.2 dB and a noise figure of 3.8 dB, while consuming a DC current of only 1.6 mA at supply voltage of 0.6 V. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A fully integrated 0.6 V low‐noise amplifier for X‐band receiver application based on 0.18 μm CMOS technology is presented in this paper. To achieve low noise and high gain with the constraint of low voltage and low power consumption, a novel modified complementary current‐reused low‐noise amplifier using forward body bias technique is proposed. A diode connected MOSFET forward bias technique is employed to minimize the body leakage and improve the noise performance. A notch filter isolator is constructed to improve the linearity of low voltage.